(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The most important areas of human life are work, knowledge, communication. Everyone knows the forms and methods of labor activity it takes years to learn the secrets, the way to improve seeks guidance. Knowing the same world, what is happening in it and also a systematic, planned time for studying the scientific and theoretical foundations of events is spent